Three thousand years of longing [videorecording (Blu-Ray)] - Miller, George, 1945 March 3-; Gore, Augusta; Swinton, Tilda; Elba, Idris; Yaşaroğlu, Erdil, 1971-; Elba, Sabrina Dhowre; Houbolt, Sarah; Özdemir, Seyithan; Lagum, Aamito; Mouawad, Nicolas; Yüksel, Ece; Hulme, Lachy, 1971-; et al. (Metro-Goldwyn-Mayer Studios Inc. ; Warner Bros. Entertainment Inc., 2022)
While attending a conference in Istanbul, Dr. Alithea Binnie happens to encounter a djinn who offers her three wishes in exchange for his freedom. This presents two problems: first, she doubts that he's real, and second, because she's a scholar of story and mythology, she knows all the cautionary tales of wishes gone wrong. The djinn pleads his case by telling her fantastical stories of his past. Eventually, she's beguiled and makes a wish that surprises them both.